A Tale of Two Writing Systems: Double Dissociation and Metalinguistic Transfer Between Chinese and English Word Reading Among Hong Kong Children. (March 2015) - Tong, Xiuli; Tong, Xiuhong; McBride-Chang, Catherine
This study investigated the rate of school-aged Chinese–English language learners at risk for reading difficulties in either Chinese or English only, or both, among second and fifth graders in Hong Kong. In addition, we examined the metalinguistic skills that distinguished those who were poor in reading Chinese from those who were poor in reading English. The prevalence of poor English readers among children identified to be poor in Chinese word recognition across the five participating schools was approximately 42% at Grade 2 and 57% at Grade 5. Across grades, children who were poor readers of both languages tended to have difficulties in phonological and morphological awareness. Poor readers of English only were found to manifest significantly poorer phonological awareness, compared to those who were poor readers of Chinese only; their average tone awareness score was also lower relative to normally developing controls. Apart from indicating possible dissociations between Chinese first language (L1) word reading and English second language (L2) word reading, these findings suggested that the degree to which different metalinguistic skills are important for reading in different writing systems may depend on the linguistic features of the particular writing system.